The fecal resistome of dairy cattle is associated with diet during nursing - Jinxin Liu (Nature Portfolio, 2019)
Livestock play a role in maintaining antibiotic resistance reservoirs. Here, Liu et al. use metagenomics to study the dynamics of antibiotic resistance genes (ARGs) in the gut of dairy cattle during early life, showing that colostrum is a potential source of ARGs and ARG abundance declines during nursing covarying with dietary transition.